Resource-based electronic feedback and its effect on the production and perception of the english consonants <r> and <h> - Manfé, Karine Pinto (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2019.